American politics, British policy: whole of life imprisonment and transatlantic influence. Issue 3 (2nd July 2016) - Pettigrew, Mark
ABSTRACT: Since the abolition of the death penalty, life imprisonment in England and Wales has had a literal meaning with exceptional rarity. Now though, in the rejection of perceived interference by the European Court of Human Rights in domestic sentencing, the politics of whole of life imprisonment have become exposed, specifically, in the widening applicability of the tariff to those who kill police officers or prison guards. Borrowing from the politics of capital punishment in the United States, in both "acting out" after a particular crime, and the prioritising of victim groups, the most severe penalty in England and Wales is increasingly beginning to mirror how the most severe punishment across the Atlantic is used, represented, and politicised.